(untitled) (Homoeopathy for All, 2024)
Nasal polyps are non cancerous, painless growths in the lining of nasal passages or sinuses. They appear as a result of chronic inflammations generally associated with asthma, allergic rhinitis, chronic sinusitis. Despite being benign, nasal polyps may cause significant discomfort, disruption of normal nasal function, nasal congestion, loss of smell and sinus infections.